Understanding Organizational Culture in an Integrated Islamic School: A Qualitative Case Study in Indonesia - Afifah Thaiyibah; Mesiono Mesiono; Syaukani Syaukani (Yayasan Sembilan Pemuda Indonesia, 2027)
This qualitative single-case study examines how organizational culture is manifested and internalized at SMP IT Al-Hijrah Islamic Global School (AIGS), Deli Serdang, Indonesia. Guided by Edgar H. Schein’s three-level framework, the study analyzes visible artifacts, espoused values, and basic underlying assumptions, together with differences in how school members understand and enact those cultural elements. The study involved 25 purposively selected participants representing school leadership, teachers, and students. Data were collected through participant observation, semi-structured interviews, and document analysis. A thematic procedure combined deductive coding based on Schein’s framework with inductive coding of patterns emerging from the field data, while source and technique triangulation supported credibility. The findings show that Islamic architecture, uniforms, language practices, rituals, and visual messages form a coherent artifact system. These artifacts are connected to espoused values of discipline, cooperation, openness, responsibility, and Islamic character. At the deepest level, members share assumptions that education is worship, knowledge should integrate religious and general learning, and service should be grounded in familial bonds. Cultural internalization was strongest among leaders and longer-serving teachers, while newer staff showed more normative and less detailed understanding. The study contributes an integrated explanation of how Islamic values move from visible practices to underlying organizational assumptions. Practically, it highlights the need for structured orientation, sustained role modeling, cultural evaluation, and stronger school-parent partnerships.